(untitled) (World Economics and Finance Bulletin, 2025)
The financial leverage effect in bank credit for ten Iraq Stock Exchange-listed commercial banks in Iraq for the period from 2005 to 2019 was studied, taking into account the dimensions of capital structure and lending levels. As well as testing the effect of debt levels on the bank’s ability to extend credit to maintain the bank’s financial sustainability. It was shown that bank credit and financial leverage had a strong negative correlation, which indicated increase in debt levels leads to a reduction in the bank’s ability to lend. The research results also showed that banks with high financial leverage adopt low and conservative lending policies, which leads to enhancing the bank’s financial capacity